Penerapan Metode Drill Play pada Gangguan Bahasa Reseptif Anak dengan Down Syndrome: Studi Kasus Tunggal - Yulidar Rusdi Rasyid; Anneta Talya Vida; Fildza Khalisha; Lisna Taufik (Jurnal Terapi Wicara, 2023)
Down syndrome is a chromosomal abnormality that occurs during the prenatal period. This condition causes a child to experience several disorders, one of which is receptive language disorder or understanding. This receptive language disorder can occur due to short-term memory impairment. Seeing this, an intervention is needed to optimise the receptive language skills of children with Down syndrome.